Organic matter restoration by conversion of cultivated land to perennial pasture on three agro-ecosystems in the Free State - Birru, Tilahun Chibsa (University of the Free State, 2002)
Understanding the process of organic matter degradation and restoration is important with regard to sustainable agricultural production on any agro-ecosystem, and of particular importance where degradation is relatively rapid, such as in the coarse textured savannah soils of the South African highveld. Organic matter degradation studies on such soils in three agro-ecosystems, Harrismith, Tweespruit and Kroonstad, have been undertaken by Du Toit et al. (1994), and Lobe et al. (2001). This study is concerned with organic matter restoration on the same agro-ecosystems, and is therefore complementary to the two earlier studies. The objective was to investigate organic matter restoration at three depths, 0-50, 50-100 and 100- 200 mm, on perennial pastures of different ages that had been established on lands which had been cultivated continuously for more than 20 years. Representative C and N values for degraded lands and virgin grasslands for the three agro-ecosystems were obtained from the studies of Du Toit et al. (1994) and Lobe et al. (2001), and used as reference values. To reduce within-site error samples were collected at six places, separated from each other by a few meters, at each site. At each of these places six subsamples of each layer were taken to make up the final sample. There were therefore 18 soil samples per site. A total of 28 sites, ranging in ages from 4 to 25 years, were identified and sampled on the three agro-ecosystems, All the samples were analyzed for C and N, and selected samples were analyzed to characterize the soil fertility levels and particle size distribution at each site. Results showed a wide variation in the rate of organic matter restoration between sites in each of the agro-eco systems , due mainly to differences in natural resource factors and management techniques. Most important of the latter was the application of N fertilizer. Where this was inadequate or absent, very low organic matter restoration rates were generally measured. An approximate threshold value of available N below which organic matter restoration is severely impaired appears to be about 15 mg kg". On pastures up to the age of25 years most of the C and N storage has been in the 0-50 mm layer, a little in the 50-100 mm layer, and very little in the 100-200 mm layer. This observation accentuates the importance of the sampling depth in such studies. These results are in accordance with those of Potter ef al. (1999). The mean C gains over all the sites in the three agroecosystems, excluding those with a Nfertility level considered too low to initiate efficient C sequestration, is 0.56 Mg ha-I yr' as compared to 0.8 Mg ha" yr" suggested by Bruce el al. (1999) for the United States of America and Canada. The relatively coarse texture of the Free State soils, and the lower aridity indices, may account for the difference. An attempt was made by pooling the data for the three agro-ecosystems, and adopting a normalization procedure, to identify common C and Nrestoration curves with time. Although a definite upward trend is visible, large inter-site variation and the shortage of data points above 20 years results in relatively low correlation coefficients and the curves being unreliable at their top end. Further research to obtain data from very old pastures is recommended, as well as ecotope specific research on benchmark ecotopes to define in a reliable way the shape of the organic matter restoration curve.

Met betrekking tot volhoubare landbouproduksie is dit belangrik om die degradasie en restorasie prosesse van organiese materiaal op enige landbou-ekosisteem te verstaan. Waar degradasie relatief vinnig is, soos op die grof getekstuurde gronde van die Suid-Afrikaanse hoëveld, is dit van spesiale belang. Du Toit et al. (1994) en Lobe et al. (2001) het organiese materiaal degradasie op sulke gronde ondersoek in die drie landbou-ekosisteme Harrismith, Tweespruit en Kroonstad. Die studie wat hier beskryf word fokus op die restorasie van organiese materiaalop dieselfde landbou-ekosisteme, en dien dus as ondersteuning vir die twee vorige studies. Die doel was om organiese materiaal restorasie op drie dieptes, 0-50, 50-100 en 100-200 mm, te ondersoek op meerjarige weidings van verskillende ouderdomme wat gevestig is op lande wat voorheen vir meer as 20 jaar onder bewerking was. Verwysingswaardes van C en N vir gedegradeerde lande en onversteurde grasveld op die drie landbou-ekosisteme is verkry uit die data van Du Toit et al. (1994) en Lobe et al. (2001). Ses monsterplekke is gebruik om die ruimtelike variasie by elke meetpunt te minirniseer. Die monsterplekke was 'n paar meter van mekaar geleë. Ses submonsters is by elke monsterplek geneem volgens 'n standaard prosedure, en dan gemeng om die finale monster op te maak. Daar was dus 18 finale grondmonsters per meetpunt. Die totale getal meetpunte op die drie landbou-ekosisteme was 28, met weidings tussen 4 en 25 jaar oud. Al die monsters is ontleed vir C en N, en geselekteerde monsters is ontleed om die grondvrugbaarheid en deeltjiegrootteverspreiding by elke meetpunt te karakteriseer. Resultate wys 'n groot variasie in die tempo van organiese materiaal restorasie op die drie landbou-ekosisteme, hoofsaaklik weens verskille in natuurlike hulpbron faktore en bestuurspraktyke. Vanlaasgenoemde is die toediening van stikstofkunsmis die belangrikste. Waar dit te min was het metings 'n baie lae tempo van organiese materiaal restorasie gewys. 'n Benaderde drumpelwaarde van beskikbare N waaronder organiese materiaal restorasie ernstig beperk word, is blykbaar naastenby 15 mg kg". Op weidings tot op die ouderdom van 25 jaar is die meeste C en N in die 0-50 mm laag gestoor, min in die 50-100 mm laag, en baie min in die 100-200 mm laag. Dit beklemtoon die belangrikheid van die diepte van monsterneming in studies van hierdie aard. Hierdie resultate stem ooreen met die van Potter et al. (1999). Die gemiddelde C toename oor al die meetpunte op die drie landbou-ekosisteme, met dié met 'n gebrek aan N uitgesluit, is 0.56 Mg ha-! jf! in vergelyking met die waarde van 0.8 Mg ha-! jr-I wat deur Bruce et al. (1999) vir die Verenigde State van Amerika en Kanada voorgestel word. Die rede vir die verskil is heelwaarskynlik die laer kleiinhoude en ariditeitsindekse van die Vrystaatse landbou-ekosisteme. Deur die data van die drie landbou-ekosisteme te poel, en met die gebruik van 'n prosedure van normalisering, is 'n poging aangewend om 'n enkel restorasiekurwe vir C en vir N te identifiseer. Alhoewel daar 'n duidelike opwaartse neiging is, is die kurwes bokant om en by 15 jaar onbetroubaar weens groot variasie tussen meetpunte van dieselfde ouderdom, en 'n gebrek aan gegewens vir weidings van meer as 20 jaar oud. Korrelasiekoeffisiente is dus relatief laag. Addisionele navorsing moet gedoen word om inligting te kry oor weidings tussen 15 en 100 jaar oud, asook op sleutel-ekotope om die vorm van die restorasiekurwe meer betroubaar te definieer.
Dissertation (M.Sc.Agric. (Soil, Crop and Climate Sciences))--University of the Free State, 2002
Keywords: Coarse-textured soils; Organic carbon; Semi-arid agro-ecosystems; Sustainable agriculture; Total nitrogen; Soils -- Nitrogen content; Agricultural ecology; Soil fertility -- South Africa -- Free State